The Power of a Social Worker in Healthcare Institutions: “Splendors and Miseries” - Vaitkevičienė, Asta; Ringienė, Vaidutė (Socialinė teorija, empirija, politika ir praktika, 2025)
The article raises the idea that the role of a social worker employed in a healthcare institution, which has remained unchanged for more than 10 years, cannot meet the full spectrum of nursing and social needs of elderly people, people with disabilities, and people with addictions. The theoretical part reviews the range of factors that increase social problems in an old age, and then these factors are backed by empirical data. The research was conducted by using a method of qualitative descriptive phenomenological analysis, revealing the structure of the experience of a social worker at a healthcare institution. The study results have revealed that social workers in healthcare institutions experience significant pressure due to a lack of inter-institutional cooperation and systemic gaps that prevent them from providing timely assistance to patients with substantial needs. An elderly client with disabilities and addictions becomes an inconvenient client – she is tossed around like a tennis ball from one service provider to another. The client rudely rejects the help offered, thus further increasing his/her social exclusion. Due to the lack of cooperation between health and social protection institutions, social workers in healthcare institutions find themselves in a challenging professional and emotional situation: they must endure strong emotional shocks and resolve ethical dilemmas. Healthcare professionals must also balance humanity with legal restrictions. The gap in legal and organizational measures prevents the needs of disabled and dependent clients from being met promptly by transferring them to a safe nursing or social care institution, and medical professionals must take the risk of exceeding the established legal norms so that the patient is not left ‘on the street’. Based on empirical data, it is concluded that the role of a social worker in a healthcare institution as an intermediary in transferring patients to nursing and social care institutions is tenuous. Social workers, apart from their personal qualities, are not provided with the necessary professional tools to ensure the smooth transfer of older adults with disabilities and alcohol dependence to a nursing and social care institution that would meet their needs.
Keywords: phenomenological analysis; social worker experience; social service organization; disabled person who consumes alcohol